Theorizing cross-lingual transfer of literacy skills among grade 1 pupils speaking same or different home and school languages - Cortez, Antoniette A. Danieles (College of Education, University of the Philippines Diliman, 2020)
The purpose of the investigation was to determine if cross-lingual transfer occurs in the vocabulary knowledge and listening comprehension skills of pupils with (1) the same home and school languages (SHSL) and (2) different home and school languages (DHSL). In addition, it tried to identify the skills which are transferrable across languages as well as determine the relationship between the pupils' literacy scores and their home literacy environment, along with parents' and teachers' attitude toward MT as MOI. A total of 160 Grade 1 pupils, 80 parents and 8 teachers from two municipalities in Iloilo were chosen based on the dominant language used in each linguistic community. Majority of the participants living in Community A speak Hiligaynon while those in Community B speak Kinaray-a. Data gathering covered three grading periods following the DepEd academic calendar of school year 2016-2017. The data gathered were subjected to Pearson Product-Moment Coefficient of Correlation to validate if there was a relationship in the pupils' literacy skills and their (1) home literacy practices, (2) parents' attitude toward the use of mother tongue as medium of instruction and (3) teachers' attitude toward the use of mother tongue as medium of instruction. To determine which group of pupils performed better in vocabulary and listening comprehension skills in MT-Hiligaynon. Filipino, and English, the t-test was used. On the other hand, qualitative data were transcribed and analyzed in order to determine the patterns based on quarterly focus group discussions with parent, individual interview with teachers, and class observations. Data analysis revealed that vocabulary knowledge sub-concepts and listening comprehension skills can be transferred across languages. Pupils from the both communities transferred almost the same vocabulary sub-concepts from MT-Hiligaynon to Filipino, Filipino to English, and MT-Hiligaynon to English. However, none of these sub-concepts were transferred across the three languages. In addition, Grade pupils from the SHSL and DHSL communities transferred similar listening comprehension skills such as predicting outcomes, sequencing events, and relating to one's experiences from Filipino to English. Notably, the pupils with different home and school languages consistently transferred the sub-skill on relating to one's experiences across the three languages. The SHSL pupils performed better than pupils with DHSL in MT-Hiligaynon and English vocabulary knowledge. However, the DHSL pupils performed better than the SHSL pupils in Filipino vocabulary knowledge. In the listening comprehensions tests, the SHSL pupils performed better than DHSL pupils when the data treated inferentially. Findings also showed that there is no relationship between the home literacy practices and parents' attitude towards MT as MOI of the SHSL and DHSL pupils' and their literacy skills (vocabulary knowledge and listening comprehension) in MT-Hiligaynon, Filipino, and English. Lastly, a significant correlation was found between the teachers' attitude toward the use of mother tongue as medium of instruction and the literacy skills of DHSL pupils in MT-Hiligaynon and Filipino. Based on the data, it can be inferred that home language is not the only major variable in learning other languages after the L1. Cross-language transfer among DHSL pupils is possible if their parents and other adults at home assume an active role in their literacy development by engaging them in shared literacy activities that are vital in achieving a strong L1 foundation. Also, empowered and resourceful teachers who create learning opportunities that promote competencies and skills developments, provide rich languages experiences, boost self-confidence during class interactions, and address ways to figure out pedagogical concerns produce remarkable achievement in the learners' academic performance. On the basis of the findings and conclusions, the study proposed a review of terminologies used in teaching Hiligaynon as MT alongside the production of learning and teaching materials aimed at developing literacy skills in the mother tongue and consequently transfer these to other languages. A major review and possibly reformation of the objectives behind the use of MT in the lower grades must be done for parents and teachers alike so that they could guide their children and pupils to value and use their mother tongue which serves as a bridge to understand concepts better. Further, the Department of Education needs to conduct a full-scale evaluation of the MTB-MLE Program by looking into how the program is being implemented at the classroom level not only by means of terminal paper and pencil assessment but also through classroom observations, and interviews. The study suggested the validation of the current study by expanding in scope to pupil's attitude and language preference. The study can also be replicated in other regions or divisions where there is an official languages used in school and there are children who speak a different language at home. Finally, a similar study can be done longitudinally until the Grade 1 participants reach Grade 3. Therefore, a reassessment may be done to test the threshold theory.